A corpus study of online reviews on The Suicide Themed Series 13 Reasons Why / Ummi Syafiqah Zaki - Ummi Syafiqah , Zaki (2020)
The present study aims to explore the reviewers’ perspectives on the suicide theme of 13 Reasons Why by examining the online reviews posted by these reviewers on Internet Movie Database (IMDb), Rotten Tomatoes, and Meta Critics. The corpus analysis tools adopted in the study are concordancing and keyword analysis. Concordancing is used to generate suicide-related concordance lines and to identify the evaluative items in the online reviews, while keyword analysis is used to explore the underlying key themes. Two frameworks applied to analyse these evaluative items and categorise them into positive and negative are evaluation in texts and discursive news values analysis (DNVA). The findings indicate that the suicide theme is perceived in negative light to a more significant extent compared to the positive light. The three main key themes that emerged from the findings and are discussed are misrepresentation of mental disorder, inaccurate portrayal of high school teenagers, and misleading message about teen social issues. The limitation of the study is the data used are limited to three review websites only while there are other websites that could contribute to the richness of the data.